PHARMACEUTICAL CONSIDERATION OF PANCHAKARMA THERAPY (International Journal of Ayurveda and Pharma Research, 2015)
Panchakarma therapy is a very important and essential part of Ayurvedic treatment. The efficacy of Panchakarma therapy depends on proper application of different elimination procedures as well as on the proper preparations of various formulations. Drugs play an important role to achieve the proper effectiveness of Panchakarma therapy. Along with the conventional Ayurvedic dosage forms, in Panchakarma therapy various modifications are made; even some unique dosage forms are also mentioned which are only applicable for Panchakarma therapy. It is inferred that these modifications of procedural pattern are for better absorption of drugs or essence of drugs with or without metabolism for elimination purpose. In this article, the dosage forms used for Panchakarma therapy; their preparation and specific modification made for Panchakarma therapy are mentioned and discussed.